KINERJA GURU AQIDAH AKHLAK, SKI, AL-QUR’AN HADITS, FIQIH DI MADRASAH TSANAWIYAH (MTs) AL-IKHLAS KEBAN II KEC. SANGA DESA KAB. MUB - M. Hasbi (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2016)
The teacher is one very important component in moving an educational institution such as madrasas. Professional teachers are also required in performing their duties as a teacher. Teacher performance as a reference to see if teachers had done their job well. Teacher performance is the ability of a teacher to carry out the task of teaching in schools / madrasah and responsible for learners under his guidance with improving learning achievement of learners. The indicators are 1) the ability of a teacher in carrying out its duties and 2) the ability displayed in the teacher or during learning activities. The performance of a teacher himself is influenced by several factors, both internal and external. Internal factors come from the teachers themselves, while external factors coming and being outside of the teacher, either directly or indirectly affect the performance embodiment. One internal factor is the competency of teachers related to the performance of its duties. External factors often influencing and shaping the internal factors.